Increased Leucocyte–Platelet Complex Formation in Recently Symptomatic versus Asymptomatic Carotid Stenosis Patients and in Micro-emboli Negative Subgroups - Murphy, Stephen J. X.; Lim, Soon Tjin; Kinsella, Justin A.; Tierney, Sean; Egan, Bridget; Feeley, T. M.; Murphy, Sinead M.; Walsh, Richard A.; Collins, D. R.; Coughlan, Tara; O'Neill, Desmond; Harbison, Joseph A.; Madhavan, Prakash; O'Neill, Sean M.; Colgan, Mary P.; Cox, Dermot; Moran, Niamh; Hamilton, George; McCabe, Dominick J. H. (Thrombosis and Haemostasis, 2019)
Introduction Cerebral micro-embolic signals (MES) predict risk of stroke in carotid stenosis patients. However, MES-negative ‘recently symptomatic patients’ also have a higher stroke risk than ‘asymptomatic patients’. Differences in platelet activation status may contribute to this disparity in risk.Methods This prospective, observational study assessed platelet biomarkers and their relationship with MES in asymptomatic versus symptomatic moderate (≥50–69%) or severe (≥70–99%) carotid stenosis patients. Full blood count parameters were measured and whole-blood flow cytometry was used to quantify platelet surface CD62P and CD63 expression and leucocyte–platelet complex formation. Bilateral simultaneous transcranial Doppler ultrasound of the middle cerebral arteries classified patients as ‘MES positive’ or ‘MES negative’.Results Data from 34 asymptomatic patients were compared with those from 43 symptomatic patients in the ‘early phase’ (≤ 4 weeks) and 37 of these symptomatic patients in the ‘late phase’ (≥ 3 months) after transient ischaemic attack/ischaemic stroke. There were no differences in %CD62P or %CD63 expression between early or late symptomatic and asymptomatic patients overall (p > 0.05). The percentage of lymphocyte–platelet complexes was higher in early symptomatic than in asymptomatic patients (2.8 vs. 2.16%; p < 0.001). MES were more commonly observed in early symptomatic (31.4%; p = 0.027) but not in late symptomatic (6.7%; p = 0.996) versus asymptomatic patients (7.1%). The percentage of lymphocyte–platelet complexes was higher in early symptomatic than in asymptomatic MES-negative patients (2.7 vs. 2.17%; p = 0.02).Conclusion These data add to the evidence that leucocyte–platelet complex formation/platelet activation is increased in recently symptomatic versus asymptomatic patients, and may contribute to the pathogenesis of first and subsequent strokes in carotid stenosis patients, including those who are MES negative.
Keywords: asymptomatic and symptomatic carotid stenosis; platelet activation; flow cytometry; lymphocyte–platelet complexes; transcranial Doppler ultrasound